Multiple myeloma treatment patterns and clinical outcomes in the Latin America Haemato‐Oncology (HOLA) Observational Study, 2008–2016 - Hungria, Vania Tietsche; Martínez‐Baños, Deborah M.; Peñafiel, Christian R.; Miguel, Carlos E.; Vela‐Ojeda, Jorge; Remaggi, Guillermina; Duarte, Fernando B.; Cao, Carmen; Cugliari, Maria S.; Santos, Telma; Machnicki, Gerardo; Fernandez, Mariana; et al. (British journal of haematology, 2020)
Summary Limited data are available regarding contemporary multiple myeloma (MM) treatment practices in Latin America. In this retrospective cohort study, medical records were reviewed for a multinational cohort of 1103 Latin American MM patients (median age, 61 years) diagnosed in 2008–2015 who initiated first‐line therapy (LOT1). Of these patients, 33·9% underwent autologous stem cell transplantation (ASCT). During follow‐up, 501 (45·4%) and 129 (11·7%) patients initiated second‐ (LOT2) and third‐line therapy (LOT3), respectively. In the LOT1 setting, from 2008 to 2015, there was a decrease in the use of thalidomide‐based therapy, from 66·7% to 42·6%, and chemotherapy from, 20·2% to 5·9%, whereas use of bortezomib‐based therapy or bortezomib + thalidomide increased from 10·7% to 45·5%. Bortezomib‐based therapy and bortezomib + thalidomide were more commonly used in ASCT patients and in private clinics. In non‐ASCT and ASCT patients, median progression‐free survival (PFS) was 15·0 and 31·1 months following LOT1 and 10·9 and 9·5 months following LOT2, respectively. PFS was generally longer in patients treated with bortezomib‐based or thalidomide‐based therapy versus chemotherapy. These data shed light on recent trends in the management of MM in Latin America. Slower uptake of newer therapies in public clinics and poor PFS among patients with relapsed MM point to areas of unmet therapeutic need in Latin America.